Firm capability assessment via the BSC and DEA. Issue 3 (22nd January 2021) - Lin, Chinho; Ting, Shu-Fang; Lee, Leslie; Lin, Sheng-Tun
Abstract : Purpose: This study proposes an objective assessment model to evaluate the performance of internal and external capabilities of firms. It facilitates firms to invest appropriate resources to cultivate the organizational capability necessary to meet the requirements of the performance indicators. Design/methodology/approach: This study integrates the concepts of resource-based theory, the organizational capability concept, and conduct a performance analysis to the four perspectives of the BSC by implementing the fuzzy set theory and data employment analysis. Findings: The findings show that the appropriate strategies help allocate available resources and capabilities during the different product life cycle, which provides practical guidelines for firms to achieve sustaining competitive advantage. Research limitations/implications: The selected factors were focused on four resources and capabilities rather than all possible factors. Originality/value: An objective assessment model was created based on internal and external competitive performance efficiency in this research field. This model facilitates the ability of the top management to make decisions for resource allocation that will enhance firm's performance.